Functional outcome and complications after treatment of moderate to severe slipped upper femoral Epiphysis with a modified Dunn procedure - Parker, Trevor Wayne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Surgical Sciences. Orthopaedic Surgery))--University of Stellenbosch, 2010.